Assessment of knowledge, attitudes and concerns to human papilloma virus vaccine among female nursing professionals in India - Rahman, Hafizur; Khalda, Ezzat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To have a successful cervical cancer control programme in developing countries, nursing staff must be aware of the facts about the disease preventive methods and the prophylactic human papilloma virus (HPV) vaccine. The aims of the present study were to assess knowledge of, attitudes toward and concerns to HPV vaccine among female Sikkimese nursing staff in India. Methods: Between April 2012 and February 2013, a pre-designed, pretested, self administered multiple responses questionnaire survey was conducted among female Sikkimese nursing staff in India. Results: Overall, 77.4% nursing staff responded that they had ever heard of a HPV vaccine. Trainee nurses were significantly more aware of the vaccine than regular working nurses. Actual knowledge of the vaccine was poor. Recommended age of HPV vaccination was aware by only 38.7% and only 30% nurses knew number of doses of vaccine, while over 90% nursing staff were not aware of time schedule of the vaccine. According to summarized knowledge index only 13.5% nurses had actual knowledge of HPV vaccine. Sixty five percent nurses wanted to vaccinate themselves or to their daughters. Top three aspects of HPV vaccine that nursing staff were most concerned were effectiveness, effect duration and long term effects. Eighty four percent nurses wanted more education and training sessions about cervical cancer prevention and HPV vaccine. Conclusions: Nursing staff in India need to be updated urgently with continuing medical education about cervical cancer prevention and HPV vaccination.